Some properties of probabilistic one-sided sticker systems - Selvarajoo, Mathuri; Fong, Wan Heng; Sarmin, Nor Haniza; Turaev, Sherzod (AENSI Publications, 2014)
Sticker systems have been introduced by Kari in 1998 as an abstract computational model which uses the Watson-Crick complementary principle of DNA molecules: starting from the incomplete double stranded sequences and iteratively using sticking operations, complete double stranded sequences are obtained. It is known that sticker systems with finite sets of axioms and sticker rules generate only regular languages. Hence, different types of restrictions have been considered to increase the computational power of sticker systems. Recently, probabilistic sticker systems have been introduced where the probabilities are initially associated with the axioms, and the probability of a generated string is computed by multiplying the probabilities of all occurrences of the initial strings in the computation of the string. In this paper, some properties of probabilistic one-sided sticker systems, which are special types of probabilistic sticker systems, are investigated. We prove that probability restriction on one-sided sticker systems can increase the computational power of the languages generated.